A cadaveric study of the three different palpation-guided techniques for glenohumeral joint injections. (December 2020) - Borbas, Paul; Eid, Karim; Ek, Eugene T; Ricks, Matthew; Feigl, Georg; Jeserschek, Julian M
Background: It is not known whether an anterior, posterior or superior approach using the Neviaser portal is more accurate for glenohumeral joint injections. The aim of this study was to evaluate the accuracy of the palpation-guided technique and compare the three different approaches. Methods: Palpation-guided glenohumeral joint injections were performed in 48 shoulders (24 cadavers) by two operators. Each shoulder was injected by three different approaches with a different coloured latex solution. The three approaches included the anterior, posterior and superior methods. The accuracy and location of unsuccessful injections were assessed through dissection of the shoulders. Results: Posterior injections were the most successful with an accuracy rate of 89.6%, followed by anterior injections (75%) and superior injections (54.2%). Both posterior ( p = 0.0001) and anterior injections ( p = 0.03) were statistically significantly more accurate than superior injections. The most common failure mode was an intratendinous or intramuscular injection, which occurred most frequently with a superior approach. Conclusions: Use of a superior approach through the Neviaser portal for the palpation-guided technique for glenohumeral joint injections showed a statistically significant inferior accuracy when compared to both the posterior and anterior approaches and is therefore not recommended. Posterior approached injections were the most accurate.